THE INFLUENCE OF CAPITAL INTENSITY AND GROWTH OPPORTUNITIES ON ACCOUNTING CONSERVATISM - Helmina BR Ginting; Rudi Ginting; Dian Ariani; Rulyenzi Rasyid; Sri Wahyuni Israfatin Bobihu (Journal of Economic, Bussines and Accounting (COSTING), 2026)
Accounting conservatism is a cautious attitude in responding to future uncertainty by recognizing expenses and liabilities as soon as possible, but only recognizing revenue and assets when they are certain to be received. Accounting conservatism in Indonesia is still very low. The purpose of this study is to find empirical evidence of the influence of capital intensity and growth opportunities on accounting conservatism. This study uses a quantitative approach using panel data regression. Using secondary data from financial reports obtained through the official website of the Indonesia Stock Exchange (IDX), the data was processed numerically. The Indonesian Consumer Cyclical Sector listed on the IDX for the 2020-2023 period constituted the study population, and a purposive sampling method was used to determine the sample size. In this study, eighty samples from twenty Consumer Cyclical Companies were selected. Eviews 12 was used for data analysis, and a random effects model (REM) was used for the research model. The results show that capital intensity does not affect accounting conservatism. Meanwhile, growth opportunities have a positive and significant effect.